Islamic Education and Vulnerable Groups Advocacy in Dayah Diniyyah Darussalam, West Aceh - M. Ikhwan; Eka Srimulyani; Sehat Ihsan Shadiqin; Tabrani ZA; M. Agus Wahyudi; Adriansyah NZ (Nazhruna: Jurnal Pendidikan Islam, 2026)
This article presents a comprehensive examination of the impact of Islamic education on vulnerable groups, particularly women and children, at Dayah Diniyyah Darussalam in West Aceh. The primary objective of this study is to explore how Islamic education functions as both a source of religious knowledge and a transformative force that empowers women and supports the development of children within the dayah environment. This research employs a qualitative, ethnographic approach. The study collects data through prolonged observation, in-depth interviews, and documentation. The data were analyzed using the iceberg analysis model throughout the research process, enabling the researchers to uncover observable practices and deeper structural and cultural patterns. The analytical process concludes with a synthesis phase to ensure that the conclusions accurately represent the overall findings. The results indicate that Islamic education at Dayah Diniyyah Darussalam extends beyond doctrinal instruction; it actively catalyzes social transformation by strengthening women’s capacities, increasing their participation in community life, and fostering a sense of agency. For children, Islamic education promotes balanced intellectual, emotional, moral, and spiritual growth. The study also emphasizes that Islamic education advocacy plays a crucial role in shaping future educational orientations and policy frameworks, particularly in contexts with similar socio-cultural characteristics. The implications of this research extend beyond West Aceh and offer valuable insights for education policymakers, Islamic education practitioners, and stakeholders seeking to adopt or adapt similar community-based educational models.